PERANCANGAN DESAIN INTERFACE PENDAFTARAN PASIEN RAWAT JALAN ONLINE VIA MOBILE DI PUSKESMAS TANJUNGANOM KABUPATEN NGANJUK - Deni Luvi Jayanto; Mohammad Bayu Dwi Saputro; Vicky Djusmin (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2022)
Outpatient registration at Tanjunganom Health Centre is done online and manually. Patients who already have BPJS can follow the online registration method, while those who use the manual method can enter Puskesmas. From the results of random interviews with several patients for manual registration, it takes a long time of around 15 minutes, from the resulted of observations, one of the causes is the registration time at the counter and the place is not wide enough, from these problems, an outpatient registration application needed online via mobile with layout, color, and control to made it easier for officers to register patients and also make it easier for patients to carry out examinations and shorten the time. This type of research is descriptive with the object being studied, namely the registration unit, for the population in the registration study and patients a number of 2 officers and 2 patients using saturated sampling. For data collection was using observation and interviews. The results of this study are an online outpatient registration application via mobile based on layout, color, and control at the Tanjunganom Health Center. Based on the online outpatient registration application via mobile, it has been adapted to the needs of officers and the application should be realized by organizing training, outreach to officers, and educational instructions for the community so that it can be more optimal in its implementation. color, and control at the Tanjunganom Health Center. Based on the online outpatient registration application via mobile, it has been adapted to the needs of officers and the application should be realized by organizing training, outreach to officers, and educational instructions for the community so that it can be more optimal in its implementation. color, and control at the Tanjunganom Health Center. Based on the online outpatient registration application via mobile, it has been adapted to the needs of officers and the application should be realized by organizing training, outreach to officers, and educational instructions for the community so that it can be more optimal in its implementation.